SND Rs1799889(-) In The Promotor Of The Plasminogen Activator Inhibitor-1 Gene Contributes To The Risk Of DVT In Women - Regina Komsa-Penkova; Georgi Golemanov; Boris Cankov; Lubomir Beshev; Petar Ivanov; Pencho Tonchev (Journal of Biomedical & Clinical Research)
The incidence of deep venous thrombosis (DVT) depends on the specific genotype, inheritance of prothrombotic polymorphisms and the influence of environmental risk factors. Rs1799889(-) polymorphism in the promotor of PAI-1 gene has been described as a risk factor for hypercoagulable state. Objective: To evaluate the contribution of thrombophilic rs1799889 (-) in the promotor of PAI-1 gene on the incidence of DVT in women and men in groups below and above 45 years of age. Тhere was significantly higher rs1799889 (-) polymorphism carriage among female patients with DVT vs controls (Chi squared =5.506, OR=2.170, p=0.021) but not in male patients (Chi squared =0.090 OR=1.147, p=0.825). A significant contribution of rs1799889 (-) polymorphism to early onset of the disease was found in female patients aged 45+ and carriers of the polymorphism (Chi squared =7.476, p=0.006), but not in young women.